1998
DOI: 10.1093/jjco/28.8.463
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemotherapy in the Elderly

Abstract: As the geriatric population is growing, it is increasingly important to be familiar with chemotherapy for the elderly. Age-related changes in pharmacokinetics are documented for doxorubicin, etoposide, ifosfamide, daunorubicin, mitomycin, cisplatin and methotrexate. The hematological toxicity of most standard-dose chemotherapy is not affected by age in patients with normal organic functions and good performance status, although increased toxicity with aging is suggested in the use of actinomycin-D, etoposide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 138 publications
0
27
0
Order By: Relevance
“…We found that a low dose of cisplatin causes necrosis in old cells whereas a high dose induces apoptosis. Actinomycin D is widely used in cancer therapy; however, its severe toxicity in old patients has been reported (52). We found that while in young cells actinomycin D induces apoptosis, in old cells it results in massive necrosis.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We found that a low dose of cisplatin causes necrosis in old cells whereas a high dose induces apoptosis. Actinomycin D is widely used in cancer therapy; however, its severe toxicity in old patients has been reported (52). We found that while in young cells actinomycin D induces apoptosis, in old cells it results in massive necrosis.…”
Section: Discussionmentioning
confidence: 73%
“…Cisplatin is one of the most effective and widely used anticancer drugs, and it is considered to have acceptable toxicity for old patients (35,38). No increased toxicity was observed in the elderly when the cisplatin dose was increased (52,58), and it was suggested that its toxicity was inversely dependent on the dose administered. We found that a low dose of cisplatin causes necrosis in old cells whereas a high dose induces apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in the omission of a median of 3 bleomycin doses in 20.8% of patients aged 40 years compared with the omission of a median of 2.5 bleomycin doses in 10.6% of the control group (Table 2). Some studies have reported increased bleomycin-related toxicity in older patients with testicular GCC, 15,16 and 1 report even suggested that bleomycin should not be used routinely in patients aged 40 years who have testicular GCC because of an increased risk of bleomycin-induced pulmonary toxicity. 17 However, this was not supported by the current study, in which the majority of patients aged 40 years tolerated full doses of bleomycin if their lung function was monitored carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Because renal function decreases physiologically with aging, (16) cisplatin use in elderly patients remains controversial. Some authors of clinical studies for patients aged 70 years or older have concluded that the use of cisplatin at moderate doses (60-100 mg/m 2 ) should be encouraged in these patients, just as it is in younger patients.…”
Section: Discussionmentioning
confidence: 99%